Three-dimensional automated measurements of femoral angles for the preoperative planning in dogs with patellar luxation - Longo, Federico; Knell, Sebastian; Nicetto, Tommaso; Savio, Gianpaolo; Pozzi, Antonio; Isola, Maurizio (Frontiers in Veterinary Science, 2024)
ObjectivesTo report the surgical outcomes of treating patellar luxation (PL) in dogs with surgical planning based on three-dimensional (3D) automated measurement of femoral angles.Study designMulticenter retrospective study.MethodsForty-one dogs with PL underwent preoperative computed tomography (CT). Three-dimensional femur models were exported as stereolithographic files, and imported into computer-aided design (CAD) software where 3D measurements were performed. The anatomical laterodistal femoral (aLDFA), femoral neck (FNA), and femoral torsion (FTA) angles were recorded. Surgical records, complications, radiographic femoral postoperative alignment, preoperative and postoperative lameness evaluation, and patellar position were reviewed. The success of the surgical outcome was based on the presence of normal patellar tracking at the last clinical recheck.ResultsForty-seven limbs were included; 46% of the cases (22/47) were affected by grade 3 PL. Mean (±SD) 3D aLDFA, FNA, and FTA measurements were 101.4° (±3.6), 132.5° (±2.6), and 17.6° (±4.3) in dogs with medial patellar luxation (MPL) and 89.3° (±7.6), 134.8° (±2.9), 36.9° (±5.3) with lateral patellar luxation (LPL), respectively. Based on the 3D preoperative planning, corrective osteotomies were performed in 34 of 47 cases. The mean radiographic follow-up was 4.7 months. At the final follow-up, PL was successfully treated in 45 of 47 cases. Patella reluxated in five cases. In three of five cases, the 3D automated plan was not followed by the surgeon.DiscussionSurgical treatment of PL based on 3D femoral measurements successfully corrected PL in 45 of 47 cases (96%). This is the first study reporting the use of 3D automated femoral angle measurement in clinical cases affected by PL.